Weed Control by Different Doses Flumioxazin Herbicide in Soybean - Kartono; Anuar Ramut; Muhammad Husaini Assauwab; Deden Sumoharjo; Muhammad Yassir; Mario Pani; Era Maulia; Yulis Untari (Warmadewa University Press, 2025)
Weed management is essential in soybean cultivation. Among the most widely practiced methods is chemical weed control using herbicides, as it is considered more effective and efficient in terms of cost, time, and labor requirements. This study aims to identify the optimal dose of flumioxazin herbicide that can effectively suppress weed growth while enhancing the growth and yield of soybean plants. This study was conducted from August to November 2024 at the Experimental Farm of the Faculty of Agriculture, Universitas Gunung Leuser, Kutacane, Southeast Aceh Regency, Aceh Province. The experiment was arranged in a non-factorial Randomized Complete Block Design (RCBD) with three replications. The treatment factor was the dose of flumioxazin herbicide, consisting of four levels: D0 = 0 g a.i ha-1, D1 = 400 g a.i ha-1, D2 = 800 g a.i ha-1, and D3 = 1200 g a.i ha-1. The observed variables included weed control percentage, weed cover, weed fresh weight, plant height, number of leaves, number of seeds per plant, and dry seed yield of soybean. The agronomic practices included the application of flumioxazin herbicide at one day after sowing (DAS) according to the respective treatment doses. The application of flumioxazin herbicide at a dose of 400 g a.i ha-1 was effective in increasing weed control percentage, reducing weed cover, and decreasing weed biomass in soybean cultivation. However, higher herbicide doses induced phytotoxic effects on soybean plants. As a result, flumioxazin application did not significantly improve plant height, number of leaves, seed number, or dry seed yield.